Offline Activism - Vishaal Sehijpaul (The Journal of Intelligence, Conflict and Warfare, 2021)
On April 23, 2021, Vishaal Sehijpaul presented at the 2021 CASIS Generation Z Congress on Offline Activism: Does It Take More than Online Social Justice Warriors? This presentation was followed by a group panel for questions and answers, whereby congress attendees were provided with an opportunity to engage in discussion with Mr. Sehijpaul. Primary discussion surrounded which types of safety were possibly more important, methods Generation Zs (Gen Zs) can adapt to potentially reduce their slacktivism, the role of government in addressing the gap between online and offline change, and whether slacktivism is relevant in current social issues, such the Black Lives Matter (BLM) movement.